2016
DOI: 10.1038/ncomms12907
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase activity is required for the proteasomal degradation of misfolded cytosolic proteins upon heat-stress

Abstract: Elimination of misfolded proteins is crucial for proteostasis and to prevent proteinopathies. Nedd4/Rsp5 emerged as a major E3-ligase involved in multiple quality control pathways that target misfolded plasma membrane proteins, aggregated polypeptides and cytosolic heat-induced misfolded proteins for degradation. It remained unclear how in one case cytosolic heat-induced Rsp5 substrates are destined for proteasomal degradation, whereas other Rsp5 quality control substrates are otherwise directed to lysosomal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 74 publications
3
50
0
Order By: Relevance
“…While Ubp3 had been known to support CytoQC under heat stress (Fang et al, 2016), our genetic screen further revealed that it supports both CytoQC and ERQC at the physiological temperature (30℃) ( Figure 1A and B). We proceeded to investigate Ubp3's functions in CytoQC, ERQC and the turnover of folded proteins.…”
Section: Ubp3 Supports Cytoqc and Erqc-lmentioning
confidence: 87%
See 1 more Smart Citation
“…While Ubp3 had been known to support CytoQC under heat stress (Fang et al, 2016), our genetic screen further revealed that it supports both CytoQC and ERQC at the physiological temperature (30℃) ( Figure 1A and B). We proceeded to investigate Ubp3's functions in CytoQC, ERQC and the turnover of folded proteins.…”
Section: Ubp3 Supports Cytoqc and Erqc-lmentioning
confidence: 87%
“…Although DUbs function in a variety of cellular activities, little is known about the spectrum of DUbs involved in QC or the exact roles of a few DUbs implicated in QC pathways, such as Ubp3 and Ubp6. Ubp3 supports CytoQC under heat stress by suppressing the conjugation of lysine 63 (K63)-linked ubiquitin chains on misfolded proteins and facilitating K48linkage (Fang et al, 2014;Fang et al, 2016;Silva et al, 2015) but its function under the physiological temperature or in other QC pathways is unknown (Oling et al, 2014). Ubp6 was proposed to delay QC because deleting UBP6 reduced the steady-state abundance of some proteins (Boselli et al, 2017;Nielsen et al, 2014;Torres et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…High temperature imposes proteotoxic stress on cells in the form of misfolded proteins and survival of this stress requires the ubiquitin-proteasome system [52][53][54][55][56] . As previously reported, pre9Δ yeast were very sensitive to high temperature 57 (Figure 5A).…”
Section: Yeast With Individual Human Proteasome Genes Grow Well In MImentioning
confidence: 99%
“…High temperature has wide-ranging effects on cells, including changes in membrane composition 64,65 , and the induction of multiple transcriptional and metabolic pathways 66,67 . Ubiquitin ligases and deubiquitinases of the ubiquitin-proteasome system are required for the degradation of proteins that misfold as a result of high temperature 55,56 . With the exception of the non-essential α3 subunit Pre9 57 , the roles of the proteasome core subunits in surviving high temperature have not been deeply investigated, in part because they are essential.…”
Section: We Can Learn From Humanized Yeastmentioning
confidence: 99%
“…Alternatively, a deubiquitinating (DUB) enzyme may team up with the HECT enzyme to edit substrates, as was shown for the yeast orthologue of the NEDD4 family, Rsp5 that mediates cytosolic protein degradation under stress conditions . Upon heat stress, Ubp2 and Ubp3 deubiquitinases associate more with Rsp5 to prevent the assembly of K63‐linked ubiquitin chains on Rsp5 substrates . K63‐modified substrates might also be recognized by other E3 ligases – yet to be discovered – that subsequently modify the chains, like in the case of SUMO‐targeted ubiquitin ligase (STUbL) family proteins .…”
Section: Selecting the Correct Ubiquitin Linkagementioning
confidence: 99%